In-situ doped and coated lithium iron phosphate material as well as preparation method and application thereof
Through the in-situ doping of high-valent metal cations in ferrous oxalate precursor and rotary kiln dynamic sintering method, the problem of poor performance of lithium iron phosphate positive electrode material during sintering is solved, and high electrochemical performance and good coating effect are achieved. .
Patent Information
- Application Number
- CN202411602824.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has problems such as overfired and raw sintering when producing lithium iron phosphate positive electrode materials, resulting in poor performance and poor discharge stability and poor coating effect in dynamic sintering.
A ferrous oxalate precursor with in-situ doped high-valent metal cations is used, and an in-situ carbon cladding layer is formed through a rotary kiln dynamic sintering method, and the sintering conditions are optimized to improve the crystallinity and electrochemical properties of the material.
The electrochemical performance of lithium iron phosphate materials is significantly improved, including high compaction density, low powder resistivity, excellent discharge specific capacity and cycle capacity retention, and is suitable for use in the positive electrode materials of lithium-ion batteries.
Smart Images

Figure CN119480983A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to an in-situ doped and coated lithium iron phosphate material and a preparation method and application thereof. Background Art
[0002] With the continuous development of electronic equipment, new energy vehicles and other industries, the application of lithium-ion batteries has become more and more extensive, among which lithium iron phosphate batteries are one of the most in-demand lithium batteries. Lithium iron phosphate cathode materials belong to olivine-type transition metal phosphates. Compared with NCM ternary cathode materials, they have the advantages of low price, environmental friendliness, long cycle life and high safety performance. At present, the market share of lithium iron phosphate cathode materials in new energy vehicles continues to increase, and it also has very broad application prospects in the field of energy storage. Its demand has exceeded that of ternary cathode materials and has become the most mainstream lithium-ion battery cathode material on the market. In recent years, many companies have continued to increase their investment in lithium iron phosphate materials, resulting in overcapacity of lithium iron phosphate and fierce competition in the industry. It is also increasingly important to reduce production costs and improve the performance of lithium iron phosphate materials.
[0003] At present, most companies mainly use high-temperature static sintering methods to produce lithium iron phosphate positive electrode materials. Commonly used sintering equipment includes tubular furnaces, box furnaces, roller kilns, etc. Static sintering of lithium iron phosphate is prone to overburning and raw burning, resulting in poor product performance, and there are problems such as low production capacity and high energy consumption. The use of rotary kilns for dynamic sintering can reduce sintering time by evenly heating the materials, with high output and low energy consumption, but at the same time it has problems such as poor discharge stability and insufficient coating effect. How to further improve the electrochemical properties of lithium iron phosphate positive electrode materials by improving the raw material ratio and preparation process is also a research difficulty in the field of lithium-ion batteries.
[0004] Therefore, it is necessary to continuously explore new preparation processes for lithium iron phosphate positive electrode materials and improve the comprehensive performance of lithium iron phosphate positive electrode materials to better meet market needs. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium iron phosphate material. The lithium iron phosphate material of the present invention has good crystallinity, good sphericity, uniform distribution of large and small particles, and excellent electrochemical properties. In addition, the material powder has a high compaction density and low powder resistivity. When used as a positive electrode material for lithium ion batteries, it has a high discharge specific capacity and cycle capacity retention rate.
[0006] The present invention also provides a method for preparing the lithium iron phosphate material.
[0007] The invention also provides a lithium ion battery positive electrode.
[0008] The invention also provides a lithium ion battery.
[0009] In a first aspect of the present invention, a lithium iron phosphate material is provided, wherein the lithium iron phosphate material comprises an in-situ carbon coating layer and a lithium iron phosphate core in-situ doped with a high-valent metal cation, and the general chemical formula of the lithium iron phosphate material is LiFe 1- x M x PO4@C, wherein 0.003≤x≤0.007, M comprises at least one of Nb, V, Ti or Y; the compaction density of the lithium iron phosphate material is in the range of 2.6 to 2.65 g / cm 3 , the powder resistivity range is 4~7Ω . cm.
[0010] According to some specific embodiments of the present invention, the lithium iron phosphate material provided by the present invention has at least the following beneficial effects:
[0011] The lithium iron phosphate material of the present invention has excellent electrochemical properties, and the compaction density of the material powder reaches 2.6g / cm 3 Above, the powder resistivity reaches 7Ω . cm or less. The lithium iron phosphate material is used as the positive electrode material of lithium-ion batteries. Its discharge specific capacity is high, with a 0.1C discharge specific capacity of more than 160mAh / g and a 1C discharge specific capacity of more than 145mAh / g. It also has a very high cycle capacity retention rate, with a capacity retention rate of more than 98% after 200 cycles at 0.1C. It has good application prospects in the field of lithium-ion batteries.
[0012] The characteristic diffraction peak of the lithium iron phosphate material of the present invention completely matches the standard characteristic peak of LiFePO4, and the peak shape is sharp and the crystallinity is good. The carbon therein is distributed in the material in the form of amorphous carbon, forming a uniform coating on the surface of the lithium iron phosphate core particles. The lithium iron phosphate material has good sphericity, uniform distribution of large and small particles, and good grading.
[0013] According to some embodiments of the present invention, the range of x in the chemical formula is 0.004≤x≤0.006.
[0014] The second aspect of the present invention provides a method for preparing the lithium iron phosphate material according to the first aspect of the present invention, comprising the following steps:
[0015] S1, preparing a mixed solution containing ferrous ions, oxalate ions, and high-valent metal cations, heating the mixed solution to react, and performing solid-liquid separation after the reaction to obtain ferrous oxalate powder in situ doped with high-valent metal cations;
[0016] S2, mixing the ferrous oxalate powder with a lithium source, a phosphorus source and a carbon source to form a slurry, and obtaining a precursor powder by grinding and spray drying;
[0017] S3, placing the precursor powder in a rotary kiln, adopting a two-stage sintering method, wherein the first stage sintering temperature is 400-500°C, the time is 1-3h, the second stage sintering temperature is 750-850°C, the sintering time is 4-6h, and after sintering, cooling and crushing are performed to obtain lithium iron phosphate material.
[0018] According to a specific embodiment of the present invention, the method for preparing the lithium iron phosphate material provided by the present invention has at least the following beneficial effects:
[0019] 1) The present invention in-situ dopes a high-valent metal cation compound in the process of synthesizing ferrous oxalate. After doping with the high-valent metal cation, the interplanar spacing of ferrous oxalate is increased, the electrochemical activity is significantly improved, and it is beneficial to the embedding of lithium ions in the subsequent sintering reaction process, and the sintering time can also be reduced. In addition, the high-valent metal cation-doped ferrous oxalate precursor of the present invention makes it easy to form lattice defects such as holes in the finished lithium iron phosphate during the dynamic sintering process, refines the grain size, shortens the lithium ion diffusion distance, and improves the ionic conductivity of the material, thereby significantly improving the capacity and cycle performance of lithium iron phosphate.
[0020] 2) The present invention further adopts a rotary kiln sintering method to sinter lithium iron phosphate material. During dynamic sintering, the material is heated evenly. When ferrous oxalate is sintered and decomposed at low temperature, a uniform carbon coating layer can be generated in situ on the surface of the lithium iron phosphate grains. The in-situ carbon coating layer with a thickness of several nanometers can, on the one hand, inhibit the abnormal growth of lithium iron phosphate grains, so that the finished particles are uniform in size and the sphericity is significantly improved and a good gradation is formed, thereby significantly improving the compaction density of the material; on the other hand, it can form a continuous conductive network with the carbon coating layer generated by the decomposition of the supplementary carbon source, and the electron conduction speed between the particles is accelerated, thereby significantly improving the electronic conductivity of the material.
[0021] 3) The process of the method of the present invention is simple and easy to control, the entire preparation process is green and environmentally friendly, and the dynamic sintering of lithium iron phosphate in a rotary kiln can effectively shorten the sintering time, significantly reduce the cost and facilitate industrial production. The ferrous oxalate precursor in situ doped with high-valent metal cations can give full play to its advantages of in-situ doping and coating dual in-situ modification in the process of dynamic sintering in a specific rotary kiln, and the prepared lithium iron phosphate positive electrode material has excellent performance.
[0022] According to some embodiments of the present invention, the source of the ferrous ions in step S1 includes at least one of ferrous sulfate or ferrous chloride.
[0023] According to some embodiments of the present invention, the high-valent metal cation in step S1 includes Nb 5+ 、V5+ 、Ti 4+ or Y 3+ At least one of .
[0024] According to some embodiments of the present invention, the temperature of the heated mixed liquid in step S1 is 60°C to 90°C.
[0025] According to some embodiments of the present invention, the concentration of ferrous ions in the mixed solution in step S1 is 0.5-2 mol / L.
[0026] According to some embodiments of the present invention, the molar ratio of ferrous ions to oxalate ions in the mixed solution of step S1 is 1:1.5-2.
[0027] The invention optimizes the ratio of ferrous ions to oxalate ions in the mixed solution, so that the obtained ferrous oxalate is more easily precipitated under the saturated oxalate ion concentration, which is beneficial to improving the reaction and production efficiency.
[0028] According to some embodiments of the present invention, the solid-liquid separation in step S1 further includes washing, drying and crushing steps.
[0029] According to some embodiments of the present invention, the lithium source in step S2 includes at least one of lithium carbonate or lithium hydroxide.
[0030] According to some embodiments of the present invention, the phosphorus source in step S2 includes at least one of phosphoric acid, diammonium phosphate or monoammonium phosphate.
[0031] According to some embodiments of the present invention, the carbon source in step S2 includes at least one of glucose, sucrose, maltose, polyaniline, polyethylene glycol, citric acid, tannic acid or polyacrylic acid.
[0032] According to some embodiments of the present invention, the mass of the carbon source in step S2 is 5% to 10% of the mass of the theoretically generated lithium iron phosphate.
[0033] According to some embodiments of the present invention, the grinding in step S2 is wet grinding using a sand mill.
[0034] According to some embodiments of the present invention, the grinding in step S2 is grinding the mixed slurry to a particle size D50 of 0.3-0.6 μm.
[0035] According to some embodiments of the present invention, the inlet air temperature of the spray drying in step S2 is 205°C to 240°C, and the outlet air temperature is 105°C to 125°C.
[0036] According to some embodiments of the present invention, the rotary kiln in step S3 is a continuous rotary kiln.
[0037] According to some embodiments of the present invention, in step S3, a lifting plate and a guide plate structure are provided in the inner cylinder of the rotary kiln, and the lifting plate structure has a bending structure.
[0038] According to some embodiments of the present invention, the heating section and the constant temperature section in the inner cylinder of the rotary kiln in step S3 are provided with a lifting plate and a guide plate structure, and the lifting plate structure has a bending structure.
[0039] The present invention further improves the rotary kiln sintering process to make it suitable for the lithium iron phosphate material preparation method of the present invention. Specifically, a specific rotary kiln cylinder is adopted, and a guide plate and a lifting plate structure are configured. The guide plate structure can prevent the material from flowing back, and the lifting plate structure can prevent the material from flowing directly and is conducive to the material turning, so that the material is heated more evenly than the general rotary kiln sintering process. The bending structure can also prevent the material from raising too much dust and prevent the material from being blown into the dust collecting bin by nitrogen. The present invention uses the improved rotary kiln sintering process to sinter the lithium iron phosphate material, which can improve the yield of the rotary kiln on the one hand, and improve the grading effect of the material on the other hand.
[0040] According to some embodiments of the present invention, the sintering in the rotary kiln in step S3 is sintering under a nitrogen atmosphere.
[0041] According to some embodiments of the present invention, the oxygen concentration in the rotary kiln in step S3 is less than 5 ppm.
[0042] According to some embodiments of the present invention, the sintering furnace pressure in the rotary kiln in step S3 is 20-50 Pa.
[0043] According to some embodiments of the present invention, the volume of the precursor powder in the rotary kiln in step S3 accounts for 10% to 20% of the volume of the cylinder of the rotary kiln.
[0044] According to some embodiments of the present invention, the inclination angle of the rotating cylinder of the rotary kiln in step S3 is 1-3°, and the rotation speed is 0.5-3.5 rpm / min.
[0045] The present invention optimizes and adjusts some parameters in the rotary kiln sintering process to better adapt to the preparation method and sintering system of this scheme, achieve better in-situ doping and coating effects, and prepare lithium iron phosphate materials with better electrochemical properties.
[0046] A third aspect of the present invention provides a lithium ion battery positive electrode, wherein the lithium ion battery positive electrode comprises the lithium iron phosphate material described in the first aspect of the present invention.
[0047] According to some embodiments of the present invention, raw materials for preparing the positive electrode of the lithium-ion battery include lithium iron phosphate material, conductive material, binder and positive electrode current collector.
[0048] According to some embodiments of the present invention, the conductive material includes acetylene black, and the binder includes polyvinylidene fluoride (PVDF).
[0049] A fourth aspect of the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery positive electrode as described in the third aspect of the present invention.
[0050] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0052] Figure 1 A cross-sectional view of a rotary kiln cylinder used in an embodiment of the present invention;
[0053] Figure 2 A cross-sectional view of a lifting plate and a guide plate inside a rotary kiln cylinder used in an embodiment of the present invention;
[0054] Figure 3 The XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0055] Figure 4 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0056] Figure 5 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 3 of the present invention;
[0057] Figure 6 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 8 of the present invention;
[0058] Figure 7 This is a SEM image of the lithium iron phosphate positive electrode material prepared in Comparative Example 10 of the present invention;
[0059] Figure 8 This is a TEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention, with a magnification of 20,000 times;
[0060] Fig. 9 This is a TEM image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention, with a magnification of 500,000 times;
[0061] Fig.10 The first charge and discharge curve of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention;
[0062] Fig.11The capacity retention rate of the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention after 200 cycles;
[0063] Figure numerals: 1-rotary kiln cylinder; 2-lifting plate; 3-guide plate. DETAILED DESCRIPTION
[0064] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0065] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0066] Example 1
[0067] This embodiment provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0068] 1) Preparation of in-situ doped ferrous oxalate:
[0069] Ferrous sulfate was dissolved in deionized water to obtain solution A, oxalic acid and niobium oxalate were dissolved in deionized water to obtain solution B, solution A and solution B were mixed to obtain a mixed solution, and the content of Fe in the mixed solution was controlled. 2+ The concentration is 1 mol / L, of which Fe 2+ , oxalate ion and Nb 5+ The molar ratio of niobium to ferrous oxalate is 0.996:1.6:0.004. The mixed solution is heated to 80°C for reaction. After the reaction, the solid and liquid are separated. The obtained solid is washed with deionized water, dried and crushed to obtain ferrous oxalate powder doped with niobium in situ, with the molecular formula of Fe 0.996 Nb 0.004 C2O4·2H2O.
[0070] 2) Preparation of precursor:
[0071] The ferrous oxalate powder doped with niobium in situ obtained in step 1) is mixed with lithium carbonate and phosphoric acid, and the ingredients are prepared according to the element molar ratio (Fe+Nb): Li: P = 1:1:1, and then polyethylene glycol is added in an amount of 8% of the theoretical mass of lithium iron phosphate to be generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45 μm, and then drying is performed using a centrifugal spray drying device (setting the inlet air temperature to 220° C. and the outlet air temperature to 110° C.) to obtain a spherical dry precursor powder.
[0072] 3) Preparation of lithium iron phosphate positive electrode material:
[0073] The precursor powder obtained in step 2) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 30Pa, the volume of the precursor powder accounts for 15% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2°, and the rotation speed is 3rpm / min. The rotary kiln sintering method of this embodiment adopts two-stage sintering: the first stage sintering temperature is 450°C, the sintering time is 2h, the second stage sintering temperature is 800°C, and the sintering time is 5h; after the sintering is completed, it is cooled and crushed to obtain the in-situ doped and coated lithium iron phosphate positive electrode material (LiFe 0.996 Nb 0.004 PO4@C);
[0074] The rotary kiln is composed of a charging bin, a replacement bin, a screw feeder, a rotary kiln air inlet and outlet, a rotating cylinder, a discharge bin, a dust collection bin, an oxygen concentration and furnace pressure test interface, wherein the furnace tube cylinder is divided into a heating section, a constant temperature section and a cooling section in sequence, wherein the constant temperature section is divided into multiple temperature zones, which can be precisely controlled in temperature. The atmosphere in the rotary kiln is pumped in through a porous air pipe at the tail of the kiln and discharged through an air pipe at the head of the kiln. The heating section and the constant temperature section in the internal cylinder 1 are provided with unique shovel plates 2 and guide plates 3, wherein the structure of the shovel plates 2 is bent downward by 45°, and there are 3 groups of shovel plates 2 on one cross section, and the shovel plates 2 are cross-arranged, and adjacent bent shovel plate groups overlap by 40%, and the guide plates 3 are spiral-shaped. The cross-sectional view of the cylinder 1 of the rotary kiln is shown as follows: Figure 1 As shown, the cross-sectional views of the internal lifting plate 2 and the guide plate 3 of the rotary kiln shell at three positions (BB, CC and DD) are as follows Figure 2 shown.
[0075] Example 2
[0076] This embodiment provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0077] 1) Preparation of in-situ doped ferrous oxalate:
[0078] Ferrous sulfate was dissolved in deionized water to obtain solution A, oxalic acid and vanadium pentoxide were dissolved in deionized water to obtain solution B, solution A and solution B were mixed to obtain a mixed solution, and the Fe content in the mixed solution was controlled. 2+ The concentration is 1 mol / L, of which Fe 2+ , oxalate ion and V 5+ The molar ratio of is 0.995:1.7:0.005, the mixed solution is heated to 70°C for reaction, the solid-liquid separation is completed after the reaction, the obtained solid is washed with deionized water, dried and crushed to obtain in-situ vanadium-doped ferrous oxalate powder, the molecular formula of which is Fe0.995 V 0.005 C2O4·2H2O.
[0079] 2) Preparation of precursor:
[0080] The in-situ vanadium-doped ferrous oxalate powder obtained in step 1) is mixed with lithium carbonate and ammonium monohydrogen phosphate, and the ingredients are prepared according to the element molar ratio (Fe+V): Li: P = 1:1:1, and then glucose is added in an amount of 7% of the theoretical mass of lithium iron phosphate to be generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45 μm, and then drying is performed using a centrifugal spray drying device (setting the inlet air temperature to 225°C and the outlet air temperature to 110°C) to obtain a spherical dry precursor powder.
[0081] 3) Preparation of lithium iron phosphate positive electrode material:
[0082] The precursor powder obtained in step 2) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 30Pa, the volume of the precursor powder accounts for 18% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2.5°, and the rotation speed is 2rpm / min. The rotary kiln sintering method of this embodiment adopts two-stage sintering: the first stage sintering temperature is 400°C, the sintering time is 2h, and the second stage sintering temperature is 850°C, and the sintering time is 4h; after the sintering is completed, it is cooled and crushed to obtain the in-situ doped and coated lithium iron phosphate positive electrode material (LiFe 0.995 V 0.005 PO4@C);
[0083] Wherein, the rotary kiln is the same as the rotary kiln in Example 1.
[0084] Example 3
[0085] This embodiment provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0086] 1) Preparation of in-situ doped ferrous oxalate:
[0087] Dissolve ferrous chloride in deionized water to obtain solution A, dissolve oxalic acid and titanyl sulfate in deionized water to obtain solution B, mix solution A and solution B to obtain a mixed solution, and control the content of Fe in the mixed solution. 2+ The concentration is 1 mol / L, of which Fe 2+ , oxalate ions and Ti 4+ The molar ratio of is 0.995:1.8:0.005, the mixed solution is heated to 80°C for reaction, the solid-liquid separation is completed after the reaction, the obtained solid is washed with deionized water, dried and crushed to obtain in-situ titanium-doped ferrous oxalate powder, the molecular formula of which is Fe 0.995 Ti0.005 C2O4·2H2O.
[0088] 2) Preparation of precursor:
[0089] The in-situ titanium-doped ferrous oxalate powder obtained in step 1) is mixed with lithium hydroxide and phosphoric acid, and the ingredients are prepared according to the element molar ratio of (Fe+Ti): Li: P = 1:1:1, and then sucrose is added in an amount of 6% of the theoretical mass of lithium iron phosphate to be generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45 μm, and then drying is performed using a centrifugal spray drying device (setting the inlet air temperature to 230°C and the outlet air temperature to 115°C) to obtain a spherical dry precursor powder.
[0090] 3) Preparation of lithium iron phosphate positive electrode material:
[0091] The precursor powder obtained in step 2) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 50Pa, the volume of the precursor powder accounts for 18% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2.5°, and the rotation speed is 2rpm / min. The rotary kiln sintering method of this embodiment adopts two-stage sintering: the first stage sintering temperature is 500°C, the sintering time is 3h, the second stage sintering temperature is 820°C, and the sintering time is 6h; after the sintering is completed, it is cooled and crushed to obtain the in-situ doped and coated lithium iron phosphate positive electrode material (LiFe 0.995 Ti 0.005 PO4@C);
[0092] Wherein, the rotary kiln is the same as the rotary kiln in Example 1.
[0093] Example 4
[0094] This embodiment provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0095] 1) Preparation of in-situ doped ferrous oxalate:
[0096] Dissolve ferrous chloride in deionized water to obtain solution A, dissolve oxalic acid and yttrium chloride in deionized water to obtain solution B, mix solution A and solution B to obtain a mixed solution, and control the content of Fe in the mixed solution. 2+ The concentration is 1 mol / L, of which Fe 2+ , oxalate ion and Y 3+ The molar ratio of yttrium to ferrous oxalate is 0.994:1.9:0.006, and the mixed solution is heated to 90°C for reaction. After the reaction, the solid and liquid are separated, and the obtained solid is washed with deionized water, dried and crushed to obtain an in-situ yttrium-doped ferrous oxalate powder with a molecular formula of Fe 0.994 Y 0.006C2O4·2H2O.
[0097] 2) Preparation of precursor:
[0098] The ferrous oxalate powder doped with yttrium in situ obtained in step 1) is mixed with lithium hydroxide and ammonium dihydrogen phosphate, and the ingredients are prepared according to the element molar ratio (Fe+Y): Li: P = 1:1:1, and then 8% of the mass of theoretically generated lithium iron phosphate is added with polyvinyl alcohol, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45 μm, and then dried using a centrifugal spray drying device (setting the inlet air temperature to 220°C and the outlet air temperature to 110°C) to obtain a spherical dry precursor powder.
[0099] 3) Preparation of lithium iron phosphate positive electrode material:
[0100] The precursor powder obtained in step 2) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 30Pa, the volume of the precursor powder accounts for 20% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2°, and the rotation speed is 3rpm / min. The rotary kiln sintering method of this embodiment adopts two-stage sintering: the first stage sintering temperature is 450°C, the sintering time is 2h, the second stage sintering temperature is 830°C, and the sintering time is 5h; after the sintering is completed, it is cooled and crushed to obtain the in-situ doped and coated lithium iron phosphate positive electrode material (LiFe 0.994 Y 0.006 PO4@C);
[0101] Wherein, the rotary kiln is the same as the rotary kiln in Example 1.
[0102] Comparative Example 1:
[0103] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that: in step 1 of this comparative example, niobium oxalate is added to control the Fe content in the mixed solution. 2+ With oxalate ion and Nb 5+ The molar ratio is 0.998:1.6:0.002.
[0104] Comparative Example 2:
[0105] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that: in step 1 of this comparative example, niobium oxalate is added to control the Fe content in the mixed solution. 2+ With oxalate ion and Nb 5+ The molar ratio is 0.992:1.6:0.008.
[0106] Comparative Example 3:
[0107] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that the second stage sintering temperature of the rotary kiln sintering in step 3) of this comparative example is 900°C.
[0108] Comparative Example 4:
[0109] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that the second sintering time of the rotary kiln sintering in step 3) of this comparative example is 9 hours.
[0110] Comparative Example 5:
[0111] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material. The difference between this comparative example and Example 1 is that the rotary kiln cylinder for sintering in the rotary kiln in step 3) of this comparative example has no guide plate structure, and its copy plate structure is four equidistant long strips embedded in the kiln.
[0112] Comparative Example 6
[0113] This comparative example provides a method for preparing a doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0114] 1) Preparation of precursor:
[0115] The ferrous oxalate powder is mixed with phosphoric acid, lithium carbonate and niobium oxalate in an element molar ratio of Li:Fe:Nb:P=1:0.996:0.004:1, polyethylene glycol is added in an amount of 8% of the theoretical mass of lithium iron phosphate, and deionized water is added for mixing and dispersion. A sand mill is used for wet grinding until the D50 particle size of the slurry is 0.45 μm, and then the slurry is dried by a centrifugal spray drying device (the inlet air temperature is set at 220°C and the outlet air temperature is set at 110°C) to obtain a spherical dry precursor powder.
[0116] 2) Preparation of lithium iron phosphate positive electrode material:
[0117] The precursor powder obtained in step 1) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 30Pa, the volume of the precursor powder accounts for 15% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2°, and the rotation speed is 3rpm / min. The rotary kiln sintering method of this comparative example adopts two-stage sintering: the first stage sintering temperature is 450°C, the sintering time is 2h, the second stage sintering temperature is 800°C, and the sintering time is 5h; after the sintering is completed, it is cooled and crushed to obtain the doped and coated lithium iron phosphate positive electrode material (LiFe 0.996 Nb 0.004 PO4@C);
[0118] Wherein, the rotary kiln is the same as the rotary kiln in Example 1.
[0119] Comparative Example 7
[0120] This comparative example provides a method for preparing a doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0121] 1) Preparation of precursor:
[0122] The ferrous oxalate powder is mixed with phosphoric acid, lithium carbonate and niobium oxalate in an element molar ratio of Li:Fe:Nb:P=1:0.996:0.004:1, polyethylene glycol is added in an amount of 8% of the theoretical mass of lithium iron phosphate, and deionized water is added for mixing and dispersion. A sand mill is used for wet grinding until the D50 particle size of the slurry is 0.45 μm, and then the slurry is dried by a centrifugal spray drying device (the inlet air temperature is set at 220°C and the outlet air temperature is set at 110°C) to obtain a spherical dry precursor powder.
[0123] 2) Preparation of lithium iron phosphate positive electrode material:
[0124] The precursor powder obtained in step 1) is placed in a nitrogen tubular atmosphere furnace, and the temperature is raised from room temperature to 800°C at a heating rate of 3°C / min for a sintering process, and the temperature is kept for 10 hours. After cooling, the powder is crushed to obtain a doped and coated lithium iron phosphate positive electrode material (LiFe 0.996 Nb 0.004 PO4@C).
[0125] Comparative Example 8
[0126] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0127] 1) Preparation of in-situ doped iron phosphate:
[0128] Ferrous sulfate was dissolved in deionized water to obtain solution A, phosphoric acid and niobium oxalate were dissolved in deionized water to obtain solution B, solution A and solution B were mixed to obtain a mixed solution, the molar ratio of Fe, P and Nb elements in the mixed solution was controlled to be 0.996:1:0.004, the mixed solution was heated to 80°C for reaction, hydrogen peroxide and sodium hydroxide were added to adjust the pH value to 1.5, the solid-liquid separation was carried out after the reaction was completed, the obtained solid was washed with deionized water, dried and crushed to obtain anhydrous iron phosphate powder doped with niobium in situ.
[0129] 2) Preparation of precursor:
[0130] The anhydrous iron phosphate powder in situ doped with niobium obtained in step 1) is mixed with lithium carbonate, and the ingredients are prepared according to the element molar ratio of Li:P=1:1, and then polyethylene glycol is added in an amount of 12% of the theoretical mass of lithium iron phosphate generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45μm, and then dried using a centrifugal spray drying equipment (setting the inlet air temperature to 220°C and the outlet air temperature to 110°C) to obtain a spherical dry precursor powder.
[0131] 3) Preparation of lithium iron phosphate positive electrode material:
[0132] The precursor powder obtained in step 2) is put into a continuous rotary kiln for sintering in a nitrogen atmosphere, the oxygen concentration of the sintering is controlled to be less than 5ppm, the sintering furnace pressure is 30Pa, the volume of the precursor powder accounts for 15% of the volume of the rotary kiln cylinder, the inclination angle of the rotating cylinder is 2°, and the rotation speed is 3rpm / min. The rotary kiln sintering method of this comparative example adopts two-stage sintering: the first stage sintering temperature is 450°C, the sintering time is 2h, the second stage sintering temperature is 800°C, and the sintering time is 5h; after the sintering is completed, it is cooled and crushed to obtain the in-situ doped and coated lithium iron phosphate positive electrode material (LiFe 0.996 Nb 0.004 PO4@C);
[0133] Wherein, the rotary kiln is the same as the rotary kiln in Example 1.
[0134] Comparative Example 9
[0135] This comparative example provides a method for preparing an in-situ doped and coated lithium iron phosphate positive electrode material, the steps are as follows:
[0136] 1) Preparation of in-situ doped iron phosphate:
[0137] Ferrous sulfate was dissolved in deionized water to obtain solution A, phosphoric acid and niobium oxalate were dissolved in deionized water to obtain solution B, solution A and solution B were mixed to obtain a mixed solution, the molar ratio of Fe, P and Nb elements in the mixed solution was controlled to be 0.996:1:0.004, the mixed solution was heated to 80°C for reaction, hydrogen peroxide and sodium hydroxide were added to adjust the pH value to 1.5, the solid-liquid separation was carried out after the reaction was completed, the obtained solid was washed with deionized water, dried and crushed to obtain anhydrous iron phosphate powder doped with niobium in situ.
[0138] 2) Preparation of precursor:
[0139] The anhydrous iron phosphate powder in situ doped with niobium obtained in step 1) is mixed with lithium carbonate, and the ingredients are prepared according to the element molar ratio of Li:P=1:1, and then polyethylene glycol is added in an amount of 12% of the theoretical mass of lithium iron phosphate generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45μm, and then dried using a centrifugal spray drying equipment (setting the inlet air temperature to 220°C and the outlet air temperature to 110°C) to obtain a spherical dry precursor powder.
[0140] 3) Preparation of lithium iron phosphate positive electrode material:
[0141] The precursor powder obtained in step 2) is placed in a nitrogen tubular atmosphere furnace, and the temperature is raised from room temperature to 800°C at a heating rate of 3°C / min for a sintering process, and the temperature is kept for 10 hours. After cooling, the powder is crushed to obtain a doped and coated lithium iron phosphate positive electrode material (LiFe 0.996 Nb 0.004 PO4@C).
[0142] Comparative Example 10
[0143] 1) Preparation of precursor:
[0144] Anhydrous iron phosphate powder is mixed with lithium carbonate, and the ingredients are prepared according to the element molar ratio of Li:P=1:1, and then polyethylene glycol is added in an amount of 12% of the theoretical mass of lithium iron phosphate to be generated, and then deionized water is added for mixing and dispersion, and wet grinding is performed using a sand mill until the D50 particle size of the slurry is 0.45μm, and then dried using a centrifugal spray drying equipment (setting the inlet air temperature to 220°C and the outlet air temperature to 110°C) to obtain a spherical dry precursor powder.
[0145] 2) Preparation of lithium iron phosphate positive electrode material:
[0146] The precursor powder obtained in step 1) is placed in a nitrogen tubular atmosphere furnace, and the temperature is increased from room temperature to 800°C at a heating rate of 3°C / min for a sintering process, and the temperature is kept for 10 hours. After cooling, the powder is crushed to obtain a lithium iron phosphate positive electrode material.
[0147] Detection of lithium iron phosphate cathode material:
[0148] 1. Detect the XRD spectrum of the lithium iron phosphate positive electrode material prepared in Example 1 as follows Figure 3 As shown in the figure, it can be seen that the characteristic diffraction peak of the sample completely matches the standard characteristic peak of LiFePO4, and the peak shape of the sample is sharp, indicating that its crystallinity is good. No diffraction peak of carbon appears in the sample, indicating that the carbon source is ultimately distributed in the sample in the form of amorphous carbon.
[0149] 2. The lithium iron phosphate positive electrode materials prepared in Example 1, Comparative Example 3, Comparative Example 8 and Comparative Example 10 were observed using a scanning electron microscope (SEM), and the corresponding Figure 4 , Figure 5 , Figure 6 and Figure 7 ,from Figure 4 It can be clearly seen that the lithium iron phosphate particles prepared in Example 1 have a better sphericity, and the size of the particles is evenly distributed to form a good gradation. Figure 7 It can be clearly seen that the sphericity of the lithium iron phosphate particles prepared in Comparative Example 10 is poor. Figure 5 and Figure 6 The sphericity of the lithium iron phosphate particles prepared in Comparative Examples 3 and 8 is also poor, which is between the lithium iron phosphate particles in Example 1 and Comparative Example 10.
[0150] 3. The lithium iron phosphate positive electrode material prepared in Example 1 was observed using a transmission electron microscope (TEM). Figure 8 (magnification 20,000 times) and Fig. 9 As shown (magnification is 500000 times), it can be seen from the figure that a carbon layer is evenly coated on the surface of the particles, and a good conductive network is formed between the evenly coated carbon layer and the lithium iron phosphate particles.
[0151] Performance Test:
[0152] The lithium iron phosphate positive electrode material prepared in each embodiment and comparative example was dissolved in N-methylpyrrolidone (NMP) with acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, stirred into a slurry and coated on an aluminum foil, and then dried and pressed to form a positive electrode material electrode sheet; metallic lithium was used as the counter electrode, 1 mol / L LiPF6 / (EC+DMC+EMC) was used as the electrolyte, and the separator was Cellgard2035. A button battery was assembled in a glove box, the battery model was CR2016, and the assembled battery was electrochemically tested using a Land battery tester, and the test voltage was 2.0-3.75V.
[0153] The compaction density and powder resistivity of the lithium iron phosphate positive electrode materials prepared in each embodiment and comparative example were tested using a Sansi Zongheng 7305 compaction density meter and a semiconductor resistivity tester (four-probe method).
[0154] The charge and discharge curve of the lithium iron phosphate positive electrode material prepared in Example 1 is as follows: Fig.10 As shown, its 0.1C discharge capacity is 160.20mAh / g, 1C discharge capacity is 145.84mAh / g, and its capacity retention rate after 200 cycles at 0.1C is as follows: Fig.11 As shown, the discharge capacity after 200 cycles at 0.1C is 158.36 mAh / g, and the capacity retention rate is as high as 98.85%.
[0155] The performance test results of the lithium iron phosphate positive electrode materials prepared in various embodiments and comparative examples are shown in Table 1.
[0156] Table 1 Performance test results of lithium iron phosphate positive electrode materials of various embodiments and comparative examples
[0157]
[0158]
[0159] The above test results show that the lithium iron phosphate positive electrode material prepared by the scheme of the present invention has excellent electrochemical performance, and the compaction density of the positive electrode material powder reaches 2.6g / cm 3 Above, the powder resistivity reaches 7Ω . cm or less, with a high discharge specific capacity, the 0.1C discharge specific capacity reaching more than 160mAh / g, the 1C discharge specific capacity reaching more than 145mAh / g, and it has a very high cycle capacity retention rate, with the capacity retention rate reaching more than 98% after 200 cycles at 0.1C.
[0160] The present invention adopts a soluble high-valent metal cation compound to perform in-situ doping in the process of synthesizing ferrous oxalate. After doping with the high-valent metal cation, the interplanar spacing of the ferrous oxalate is increased, the electrochemical activity thereof is significantly improved, and the embedding of lithium ions in the subsequent sintering reaction process is facilitated, and the sintering time can also be reduced. During the dynamic sintering process, the high-valent metal cation-doped ferrous oxalate precursor of the present invention makes it easy to form lattice defects such as holes in the finished lithium iron phosphate, refines the grain size, shortens the lithium ion diffusion distance, and improves the ionic conductivity of the material, thereby significantly improving the capacity and cycle performance of the lithium iron phosphate.
[0161] The present invention further adopts a rotary kiln sintering method to sinter the lithium iron phosphate material. During the dynamic sintering, the material is heated evenly. When ferrous oxalate is sintered and decomposed at a low temperature, a uniform carbon coating layer can be generated in situ on the surface of the lithium iron phosphate grains. The in-situ carbon coating layer with a thickness of several nanometers can, on the one hand, suppress the abnormal growth of the lithium iron phosphate grains, so that the finished particles are uniform in size and the sphericity is significantly improved and a good gradation is formed, thereby significantly improving the compaction density of the material; on the other hand, it can form a continuous conductive network with the carbon coating layer generated by the decomposition of the supplementary carbon source, and the electron conduction speed between the particles is accelerated, thereby significantly improving the electronic conductivity of the material.
[0162] The present invention further improves the rotary kiln sintering method by adopting a specific rotary kiln cylinder structure, wherein the guide plate can prevent the material from flowing back, the lifting plate structure can prevent the material from flowing directly and is conducive to the material turning, so that the material is heated more evenly than the general rotary kiln sintering material, and the bending structure can also prevent the material from raising too much dust and prevent the material from being blown into the dust collecting bin by nitrogen. The present invention uses an improved rotary kiln sintering process to sinter lithium iron phosphate material, which can improve the yield of the rotary kiln on the one hand and improve the grading effect of the material on the other hand.
[0163] The method of the present invention is simple and easy to control, the entire preparation process is green and environmentally friendly, and the lithium iron phosphate is dynamically sintered in a rotary kiln, which can effectively shorten the sintering time, significantly reduce the cost and facilitate industrial production. The ferrous oxalate precursor in situ doped with high-valent metal cations can give full play to its advantages of in-situ doping and coating dual in-situ modification in the process of dynamic sintering in a specific rotary kiln, and the prepared lithium iron phosphate positive electrode material has excellent performance.
[0164] Compared with Example 1, the doping amount of the high-valent metal cations doped in situ in Comparative Examples 1 and 2 is too low and too high, respectively, which will affect the lithium iron phosphate positive electrode material finally prepared. The doping amount of the high-valent metal cations in Comparative Example 1 is too low, so the activity of the ferrous oxalate obtained is low, and the conductivity of the positive electrode material finally prepared is also poor. The doping amount of the high-valent metal cations in Comparative Example 2 is too high, which will inhibit the growth of lithium iron phosphate particles, and the compaction density of the material is low, which will lead to a decrease in the energy density of the material. In the preparation methods of Comparative Examples 3 and 4, the sintering temperature and time of the second stage of sintering in the rotary kiln are too high and too long, respectively, which will cause the particles of the material to grow further. When the particles of the material are too large, the diffusion distance of lithium ions is long and the impedance is large, so that its capacity is low, thereby deteriorating its electrochemical performance.
[0165] The rotary kiln cylinder of comparative example 5 has no guide plate structure, and the shovel plate structure is four equidistant strips embedded inside the kiln. The internal cylinder structure of the rotary kiln will affect the uniformity of heating of the material during sintering. The embodiment uses the improved rotary kiln sintering process of the present invention to further optimize the doping uniformity and carbon coating effect. The specific rotary kiln dynamic sintering preparation process of the present invention is used on the basis of the ferrous oxalate precursor doped with high-valent metal cations in situ, which can give full play to the advantages of in-situ doping and coating dual in-situ modification, thereby significantly affecting the material properties. In addition, the rotary kiln dynamic sintering process is used to sinter lithium iron phosphate, which can effectively shorten the sintering time, reduce production costs, and facilitate industrial production.
[0166] The preparation methods of Comparative Examples 6 and 7 differ from those of the embodiment in terms of process flow. They do not first prepare ferrous oxalate powder doped with high-valent metal cations in situ, but directly mix and sinter ferrous oxalate, phosphorus source, lithium source, high-valent metal cation compound and carbon source, which makes it difficult to better promote the improvement of the electrochemical performance of lithium iron phosphate positive electrode materials. In addition, the sintering of Comparative Example 7 uses a conventional nitrogen tubular atmosphere furnace for one-time sintering, so the electrochemical performance of the prepared lithium iron phosphate positive electrode material is worse.
[0167] The preparation methods of Comparative Examples 8 and 9 also differ from those of the examples in terms of process flow, in that they first prepare ferric phosphate doped with high-valent metal cations in situ, and then mix and sinter it with a lithium source and a carbon source. This process lacks an intermediate process for preparing ferrous oxalate doped with high-valent metal cations in situ, and it is difficult to achieve a better in-situ coating effect, thereby affecting the finished product performance of the lithium iron phosphate positive electrode material. Comparative Example 10 uses conventional ferric phosphate as a precursor and adopts a tubular furnace for sintering, which makes it difficult to achieve a better in-situ doping and coating effect, so the performance of the sintered finished product is the worst.
[0168] In summary, the present invention uses ferrous oxalate doped with high-valent metal cations as a precursor and uses a rotary kiln for dynamic sintering to better exert the effects of in-situ doping and coating, significantly improving the performance of the finished lithium iron phosphate product. The lithium iron phosphate positive electrode material prepared by the scheme of the present invention has excellent electrochemical properties, and the lithium ion battery prepared using the same has a high discharge specific capacity and a high cycle capacity retention rate, and has a good application prospect.
[0169] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A lithium iron phosphate material, characterized in that: The lithium iron phosphate material comprises an in-situ carbon coating layer and an in-situ doped lithium iron phosphate core with high-valent metal cations. The general chemical formula of the lithium iron phosphate material is LiFe 1-x M x PO4@C, wherein 0.003≤x≤0.007, and M comprises at least one of Nb, V, Ti or Y; The compaction density of the lithium iron phosphate material is in the range of 2.6 to 2.65 g / cm 3 , the powder resistivity range is 4~7Ω . cm.
2. The method for preparing the lithium iron phosphate material according to claim 1, characterized in that: The following steps are involved: S1, preparing a mixed solution containing ferrous ions, oxalate ions, and high-valent metal cations, heating the mixed solution to react, and performing solid-liquid separation after the reaction to obtain ferrous oxalate powder in situ doped with high-valent metal cations; S2, mixing the ferrous oxalate powder with a lithium source, a phosphorus source and a carbon source to form a slurry, and obtaining a precursor powder by grinding and spray drying; S3, placing the precursor powder in a rotary kiln, adopting a two-stage sintering method, wherein the first stage sintering temperature is 400-500°C, the time is 1-3h, the second stage sintering temperature is 750-850°C, the sintering time is 4-6h, and after sintering, cooling and crushing are performed to obtain lithium iron phosphate material.
3. The preparation method according to claim 2, characterized in that: The molar ratio of ferrous ions to oxalate ions in the mixed solution of step S1 is 1:1.5-2.
4. The preparation method according to claim 2, characterized in that: The high-valent metal cation in step S1 includes Nb 5+ 、V 5+ 、Ti 4+ or Y 3+ At least one of .
5. The preparation method according to claim 2, characterized in that: The lithium source in step S2 includes at least one of lithium carbonate or lithium hydroxide.
6. The preparation method according to claim 2, characterized in that: The phosphorus source in step S2 includes at least one of phosphoric acid, diammonium phosphate or monoammonium phosphate.
7. The preparation method according to claim 2, characterized in that: The carbon source in step S2 comprises at least one of glucose, sucrose, maltose, polyaniline, polyethylene glycol, citric acid, tannic acid or polyacrylic acid; Preferably, the mass of the carbon source in step S2 is 5% to 10% of the mass of the theoretically generated lithium iron phosphate.
8. The preparation method according to claim 2, characterized in that: In step S3, a lifting plate and a guide plate structure are arranged in the inner cylinder of the rotary kiln, and the lifting plate structure has a bending structure.
9. A lithium-ion battery positive electrode, characterized in that: Including the lithium iron phosphate material as described in claim 1.
10. A lithium ion battery, characterized in that The lithium-ion battery positive electrode comprises the positive electrode of claim 9.
Citation Information
Cited By
Organic framework in-situ derived low-energy-gap lithium iron phosphate material and application thereof
CN120709334A
Lithium iron phosphate positive electrode material and preparation method therefor, and lithium battery
WO2026199909A1